Differences, similarities and changes of national identity signs in print advertisements - Zantides, Evripides (My University, 2018)
Advertisements prevail in everyday culture not only through the traditional mediums of television, radio, magazines or public billboards but also through pop-up menus or side bars of web pages on the internet. Their intensive presence in public discourse makes them part of popular culture and this allows us to study them as objects that reproduce national identity because of their quotidian manifestation in everyday social interaction, practices, habits and routines (Edensor, 2002). From a similar perspective, Anderson (2006) embraces the reading of advertisements as a practice that cultivates nationhood. Under his theoretical framework, people are having a sense of belonging to an imagined political community because they share the same readings in everyday life. The current paper aims to identify what kinds of nonverbal signs that conceptualise national identity are portrayed in print advertisements of the Republic of Cyprus since state independence from 1960 to 2010, as well as which ones are prevailing in an overall corpus of n=1860 advertisements. A methodological approach that utilizes quantitative content analysis and qualitative analysis, based on a semiotic interpretation of advertisements is implemented to withdraw results. While the findings of the study depict predominant cultural values and characteristics of the Cypriot national identity, a mapping of the nonverbal signs over time portrays which ones are affected or not, throughout the socio-political development of the island as a post-colonial, independent state. The paper shows that national credentials in print advertisements can, on the one hand, reflect values and characteristics of the people in a given culture, and on the other, portray differences, similarities and changes of locality in a reciprocal way over time.
Keywords: Semiotics; National identity; Advertising; Typography; Graphic design